Artificial Intelligence as a Catalyst for Modernizing Islamic Family Law - Mawaddah, Mawaddah; Alwi, Alwi; Ustman, Najamudin Ali; Lahada, Akmal M.; Dita, Dita (IAIN Manado, 2024)
This research examines the integration of artificial intelligence (AI) in collective ijtihad in Islamic family law, looking for innovative ways to integrate modern technology with Sharia principles. Using a qualitative approach, data was collected through in-depth interviews and focused group discussions with Islamic law experts and AI practitioners and through analysis of relevant legal documents and literature. The study's findings show that AI can speed up the ijtihad process and increase efficiency and accuracy in analyzing and resolving complex family law cases. This research reveals that although AI brings many benefits, its use must still consider compliance with sharia values, with strict ethical supervision. The discussion in this study emphasizes the importance of a balance between technological innovation and adherence to Islamic principles. The conclusions of this study suggest that the use of AI in collective ijtihad not only opens up new possibilities in the practice of Islamic law but also challenges scholars to evaluate and possibly adapt traditional principles to ensure that they remain relevant in a rapidly changing social and technological context.